Goodbye college - hello life! : go-to answers from a got-there grown-up - Brock, Lisa (HRD Press, 2009)
Do you know a high school or university student on the edge of adulthood? Chances are, they know they need to grow up and begin to find out who they are and what they need to do to get where they want to go. But it's a time of doubt, worry and even fear. That's where this book can be extremely helpful. Goodbye College - Hello Life is that little voice that nudges young people and encourages them to trust themselves, take a chance and believe that they can do it. The author - a businesswoman, coach, religious teacher and "grown-up" - is a cheerleader for young people dedicated to helping them find their voice, courage, vision and way. She encourages young readers to present their physical self and their mental self professionally, dress appropriately and behave appropriately, be respectful of others when it comes to technology, listen every now and then to others and themselves - all sound advice that will pay off in many ways throughout their life.